Preparation and evaluation of ofloxacin-loaded palmitic acid solid lipid nanoparticles - Shuyu Xie (Dove Medical Press, 2011)
Shuyu Xie, Luyan Zhu, Zhao Dong, Yan Wang, Xiaofang Wang, WenZhong ZhouDepartment of Preventive Veterinary Medicine, College of Veterinary Medicine, China Agricultural University, Beijing, People’s Republic of ChinaAbstract: The purpose of this study was to use solid lipid nanoparticles (SLN) to improve the pharmacological activity of ofloxacin. Ofloxacin-loaded SLN were prepared using palmitic acid as lipid matrix and poly vinyl alcohol (PVA) as emulsifier by a hot homogenization and ultrasonication method. The physicochemical characteristics of SLN were investigated by optical microscope, scanning electron microscopy, and photon correlation spectroscopy. Pharmacokinetics was studied after oral administration in mice. In vitro antibacterial activity and in vivo antibacterial efficacy of the SLN were investigated using minimal inhibitory concentrations (MIC) and a mouse protection model. The results demonstrated that the encapsulation efficiency, loading capacity, diameter, polydispersivity index, and zeta potential of the nanoparticles were 41.36% ± 1.50%, 4.40% ± 0.16%, 156.33 ± 7.51 nm, 0.26 ± 0.04, and –22.70 ± 1.40 mv, respectively. The SLN showed sustained release and enhanced antibacterial activity in vitro. Pharmacokinetic results demonstrated that SLN increased the bioavailability of ofloxacin by 2.27-fold, and extended the mean residence time of the drug from 10.50 to 43.44 hours. Single oral administrations of ofloxacin-loaded nanoparticles at 3 drug doses, 5 mg/kg, 10 mg/kg, and 20 mg/kg, all produced higher survival rates of lethal infected mice compared with native ofloxacin. These results indicate that SLN might be a promising delivery system to enhance the pharmacological activity of ofloxacin.Keywords: ofloxacin, pharmacological activity, solid lipid nanoparticles, antibacterial activity